Counseling and application of personal protective equipment to reduce work accidents in welding workshops - Chauliah Fatma Putri; Ngudi Tjahjono (University of Merdeka Malang, 2022)
Dinoyo Welding Workshop is one of the welding workshops located in Dinoyo, Lowokwaru, Malang City. The workshop is quite small with an owner and 3 employees. Even so, this workshop does have a lot of customers. Understanding and awareness of Occupational Safety and Health (OHS), especially in the use of Personal Protective Equipment (PPE) here was heavily ignored, causing the frequent occurrence of work accidents. The purpose of this activity was to reduce the occurrence of accidents and occupational diseases when doing work and to instill the understanding of workers regarding the importance of OHS aspects, especially the use of PPE. The method used was the Participatory Rural Appraisal (PRA) method by conducting OHS counseling and training as well as training on the use of PPE in the welding workshop. This activity caused work accidents to decrease significantly with an average decrease rate of 69.44% The occurrence of work accidents met the highest decrease in work accidents caused by fire on the skin which became 0 events, which means accidents did not happen anymore because of fire, as well as accidents that occurred in the eye due to metal splash and fire sparks. The next highest decreases are the occurrence of hot welding fires, breathing problems due to welding fumes, scratches, and red eyes.